Hyperglycemia and Physical Impairment in Frail Hypertensive Older Adults - Pansini, Antonella; Lombardi, Angela; Morgante, Maria; Frullone, Salvatore; Marro, Anna; Rizzo, Mario; Martinelli, Giuseppe; Boccalone, Eugenio; De Luca, Antonio; Santulli, Gaetano; Mone, Pasquale (Frontiers in Endocrinology, 2022)
BACKGROUND: Frailty is a multidimensional condition typical of elders that determines physical decline. Frail older adults have a high-risk of functional decline, hospitalization, and mortality. Hyperglycemia (HG) is frequently observed in frail older adults, and it represents an independent predictor of worst outcomes, with or without diabetes mellitus (DM). We aimed to study the impact of hyperglycemia on physical impairment in frailty. METHODS: We studied consecutive older adults with frailty and hypertension at the ASL (local health authority of the Italian Ministry of Health) of Avellino, Italy, from March 2021 to September 2021. Exclusion criteria were: age< 65 years, no frailty, no hypertension, left ventricular ejection fraction <25%, previous myocardial infarction, previous primary percutaneous coronary intervention and/or coronary artery bypass grafting. All patients practiced blood samples for glycemia, HbA1c and creatinine. A physical frailty assessment was performed following the Fried Criteria; additionally, we performed a 5-meter gait speed (5mGS) test in all patients. RESULTS: 149 frail patients were enrolled in the study, of which 82 had normoglycemia (NG), 67 had HG. We observed a significantly slower 5mGS in the HG group compared to the NG group (0.52±0.1 vs. 0.69±0.06; p<0.001). We found a strong and significant correlation between 5mGS and glycemia (r: 0.833; p<0.001). We performed a multivariate analysis with 5mGS as a dependent variable in all patients, yielding a significant association for glycemia (p<0.001) and COPD (p: 0.043). CONCLUSIONS: HG drives physical impairment independently from DM.